2008
DOI: 10.1002/macp.200700418
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Hemolytic Activities of Quaternary Pyridinium Functionalized Polynorbornenes

Abstract: In this study, amphiphilic polyoxanorbornene with different quaternary alkyl pyridinium side chains were synthesized. The biological efficiencies of these polymers, with various alkyl substituents, were determined by bacterial growth inhibition assays and hemolytic activity (HC 50 ) against human red blood cells (RBCs) to provide selectivity of these polymers for bacterial over mammalian cells. A series of polymers with different alkyl substituents (ethyl, butyl, hexyl, octyl, decyl and phenylethyl) and two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
163
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(170 citation statements)
references
References 49 publications
4
163
0
Order By: Relevance
“…A SMAMP with an MIC 90 of 4 mg mL properties of a high HC 50 value and a low MIC 90 lead to the desired high selectivity. 3 Magainin (MSI 78), a frog host defense peptide, has a selectivity of 10, [8] and human defensins are even more selective (> 40 for nNP-1, [9] > 100 for human b-defensin 3 [10] ). Several studies investigating structureproperty relationships of SMAMPs have highlighted the importance of an appropriate amphiphilicity: [8,[11][12][13][14] a polymer with too much hydrophobicity will be toxic to mammalian cells, yet too little hydrophobicity will render it inactive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A SMAMP with an MIC 90 of 4 mg mL properties of a high HC 50 value and a low MIC 90 lead to the desired high selectivity. 3 Magainin (MSI 78), a frog host defense peptide, has a selectivity of 10, [8] and human defensins are even more selective (> 40 for nNP-1, [9] > 100 for human b-defensin 3 [10] ). Several studies investigating structureproperty relationships of SMAMPs have highlighted the importance of an appropriate amphiphilicity: [8,[11][12][13][14] a polymer with too much hydrophobicity will be toxic to mammalian cells, yet too little hydrophobicity will render it inactive.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigating structureproperty relationships of SMAMPs have highlighted the importance of an appropriate amphiphilicity: [8,[11][12][13][14] a polymer with too much hydrophobicity will be toxic to mammalian cells, yet too little hydrophobicity will render it inactive. [8,13,[15][16][17] To complement these reports, the aim of this paper is: 1) to first study the effect of different organic counterions of a model SMAMP on its antimicrobial properties, and 2) to subsequently investigate the influence of molecular charge density on the antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was successfully applied to the development of new types of polymer antimicrobials over the last decade, including copolymers of β-lactams [27], polynorbornenes [28], polymethacrylates [29,30], and polystyrenes [31]. Further fine-tuning of the polymers' physiochemical properties by modifying the cationic functionality, amphiphilic balance, and polymer sizes has yielded favorable improvements in antimicrobial activity and selective toxicity to bacteria relative to human red blood cells [30,[32][33][34][35]. In addition to these examples of peptidomimetic polymers, it has been recently reported that several other polymer scaffolds such as oligo(oxazoline)s [36], PEGylated poly(vinyl pyridine)s [37], and polyoxetanes with quaternary ammonium and PEG-like side chains [38] display antibacterial activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen clearly that with the increase of carbon number in the alkyl chain, antibacterial activity of the treated silk fabrics is generated, which is in accordance with other studies. 24 As for Gramnegative bacteria E. coli, 100% of these bacteria were killed within 60, 10, and 10 min for samples of silk-g-C 8 , silk-g-C 12 , and silk-g-C 18 , respectively. In the Exp 2, samples of silk-g-C 8 could only inactivate 94.98% (1.30 logs reduction) and 93.45% (1,18 logs reduction) of S. aureus and E. coli O157:H7, respectively, within 60 min.…”
Section: Antibacterial Testmentioning
confidence: 99%